Biomarker of early neurological deterioration in minor stroke and proximal large vessel occlusion: A pilot study - Wang, Zhiqiang; Wang, Shuai; Li, Yuxia; Wang, Rongyu; Jiang, Lianyan; Zheng, Bo; Zhang, Yaodan; Wang, Qingsong; Wang, Jian (Frontiers in Neurology, 2022)
Background Plasma neurofilament light chain (pNFL) represents one of the scaffolding proteins of central nervous system axonal injury. The aim of this study was to evaluate pNFL as a predictive biomarker for early neurological deterioration (END) in medically managed patients with large vessel occlusion (LVO) and mild presentation (NIHSS < 6). Methods This retrospective study was developed from a prospectively collected stroke database, which was conducted at a large academic comprehensive stroke center in western China. Patients who first presented with acute ischemic stroke (AIS) within 24 h of symptom onset were continuously included. Stroke severity was analyzed at admission using the NIHSS score. The pNFL drawn on admission was analyzed with a novel ultrasensitive single-molecule array. Results Thirty-nine consecutive patients were included in the analysis, and 19 (48.72%) patients experienced END. Patients who experienced END had significantly higher pNFL levels (mean, 65.20 vs. 48.28 pg/mL; P < 0.001) and larger infarct volume (mean, 15.46 vs. 9.56 mL; P < 0.001). pNFL was valuable for the prediction of END (OR, 1.170; 95% CI, 1.049–1.306; P = 0.005), even after adjusted for age and sex (OR, 1.178; 95% CI, 1.038–1.323; P = 0.006), blood sampling time, baseline NIHSS, TOAST classification, and infarct volume (OR, 1.168; 95% CI, 1.034–1.320; P = 0.012). The area under the ROC curve was 85.0% (95% CI, 0.731–0.970; P < 0.001). The sensitivity was 73.7%, and the specificity was 80%. Conclusion END in minor stroke with LVO was distinguishable from those without END following the determination of pNFL in the blood samples within 24 h of onset. The pNFL is a promising biomarker of END in minor stroke with LVO. Clinical trial registration ChiCTR1800020330.